COMPARISON OF CONTROL CHART X ̅ BASED ON MEDIAN ABSOLUTE DEVIATION WITH S - Mayashari, Mayashari; Herdiani, Erna Tri; Anisa, Anisa (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2024)
A stable and controlled process will produce products of good quality following predetermined specifications. A control chart is one of the statistical tools that can be used to measure the stability of a product process in a controlled state. Control charts commonly used to evaluate the statistical control process are Shewhart control charts ( and ). The control chart is used to control the process, as seen from the average and variability of the process. If the data used is not normally distributed or there are outliers, then an alternative control chart, namely the Median Absolute Deviation (MAD), can be used. MAD is used to monitor the process mean and process standard deviation because it has properties that are robust or resistant to deviations. This research aims to form a control chart based on MAD, apply it to data on fat content in animal feed products, and compare control charts based on with the control chart based on control chart based on MAD. The limitations in this study are the quality characteristics used consist of only one variable and the data is not normally distributed, only limited to the mean process, and the data used in this study are observation data on the fat content contained in animal feed products at PT Japfa Comfeed Indonesia Tbk Makassar Unit from December 2021 to January 2022. The results of this study show that the control chart based on MAD detects more out-of-control points than the control based on . The performance of the control chart based on MAD is better at detecting changes in the process than the control chart based on because it has a relatively smaller ARL value.